Doramectin treatment of myiasis by Cochliomyia hominivorax in a captive ocelot (Leopardus pardalis): A case report - Pulgar H., Ernesto; Quijada Pinango, Jessica Johanna; Bethencourt, Angélica; Moissant de Román, Elena (ENTOMOTROPICA, 2011)
A myiasis produced by blowfly larvae (Calliphoridae: Cochliomyia hominivorax) in a captive wild ocelot (Leopardus pardalis) is presented. This captive feline lives in the “Zoológico Las Delicias”, at Maracay, Aragua State, Venezuela. The myiasis was post-traumatical in a wound in the feline’s front left member. Due to the feline’s particular sensitivity to the toxicity of most pour-on insecticides, and the fact that sedation is necessary for its handling; the larvae were extracted and a single dose of doramectin (200 μg/Kg of live weigth) was administered. Myiasis remission was observed, without damage to the feline health. This is the first case of treatment of a myiasis produced by Cochliomyia hominivorax in a Leopardus pardalis, using the endectocide Doramectin in Venezuela